The Impact of Response Instruction and Target Group on the BIAS Map - Findor, Andrej; Lášticová, Barbara; Hruška, Matej; Popper, Miroslav; Váradi, Luca (Frontiers in Psychology, 2020)
Response instructions—inviting participants to respond from a certain perspective—can significantly influence the performance and construct validity of psychological measures. Stereotype Content Model (SCM) and then the BIAS map (“behaviours from intergroup affect and stereotypes”) were originally developed as universal measures of shared cultural stereotypes—participants’ perceptions of what most of the people in a society think about the target group—and their related social-structural antecedents, emotions and behavioural tendencies. Yet a number of studies have adopted a different response instruction focusing on individual stereotypes—what the participants personally think about the target group. So far, there is little evidence to suggest how these two different response instructions (individual vs shared cultural perspective) might influence the performance of the BIAS map, especially when applied to target groups that elicit different normative and social desirability concerns. To provide novel evidence, we conducted an experiment with a representative sample of ethnic Slovaks (N = 1269). In a 2x2 factorial design, we found response instruction (individual vs shared cultural perspective) and target group (stigmatised ethnic minority (the Roma) vs non-stigmatised ethnic minority (the Hungarians)) had significant effects on the BIAS map and their interaction had significant effects on the social structure and behavioural tendencies (but not on stereotypes and emotions) scales. Exploratory analysis also points to partial influence on the mediation hypothesis underlying the BIAS map and minor effects on its scale properties. Our evidence suggests that the difference between individual stereotypes and shared cultural stereotypes partially depends on the target group in question and that they should be treated as two potentially separate constructs.